HealthShield: A Blockchain-Based Electronic Health Recording System with Enhanced Security Algorithm for Immutable and Confidential Health Data Management (International Journal of Scientific Research in Science and Technology, 2024)
This research introduces an Electronic Health Recording System (EHRS) fortified with the HealthShield security algorithm and blockchain technology to enhance the security, integrity, and accessibility of electronic health records (EHRs). HealthShield integrates Argon2, AES, PBFT, and MFA algorithms, surpassing the limitations of conventional SHA-256 encryption. Leveraging Angular, Truffle, Solidity, IPFS, Django, and MySQL, the EHRS offers a robust framework for secure, transparent, and decentralized health data management. The proposed system ensures the immutability and transparency of health records, fostering trust among stakeholders while mitigating the risks associated with centralized data repositories. It prioritizes user experience with a user-friendly interface, facilitating seamless interaction for healthcare professionals, patients, and administrators. Distinguishing itself from existing systems, the EHRS combines HealthShield and blockchain technology to redefine data security standards in healthcare, adhering to regulatory frameworks to uphold patient privacy and compliance. Scalability considerations accommodate the evolving needs of healthcare institutions, ensuring optimal performance and efficiency in data processing. Through empirical evaluation and real-world deployment scenarios, the efficacy and viability of the proposed system are validated, paving the way for transformative innovations in healthcare informatics. This research contributes to advancing EHRS systems by presenting a comprehensive framework that safeguards health data while enhancing accessibility, transparency, and integrity. In summary, this research contributes to advancing EHRS systems by presenting a comprehensive framework that safeguards health data while enhancing accessibility, transparency, and integrity. By integrating HealthShield and blockchain technology, the proposed EHRS sets new standards for data security in healthcare, promising significant impact on patient care and healthcare management.
Keywords: Electronic Health Recording System; Healthshield Security Algorithm; Electronic Health Records; Blockchain Technology; Argon2; AES; PBFT; MFA Algorithms; Angular; Truffle; Solidity; IPFS; Django; MySQL; Security; Transparency; Integrity; Decentralized Data Management; User Experience; Healthcare Informatics